0834 Comparing Sleep Quality between Caucasian and Minority Patients with Inflammatory Bowel Disease. (12th April 2019) - Hammer, David A; Wu, Ting; Auerbach, Sanford; Qazi, Taha; Farraye, Francis A
Abstract: Introduction: Patients with inflammatory bowel disease (IBD) have an increased incidence of fatigue and sleep disturbances. Previous research has suggested that minority patients with IBD are more likely to report poor sleep quality compared to Caucasians, though objective data in support of this is lacking. In this prospective, cross-sectional study, we use actigraphy to compare sleep quality among minority (Hispanic and African American) and Caucasian patients with IBD. Methods: 50 patients with a confirmed diagnosis of IBD were recruited. Exclusion criteria included a known history of a sleep disorder or a Charlson Comorbidity Index greater than or equal to 3. Subjects were grouped as either Caucasian or a minority. Patients were asked to complete the PROMIS-8a SD short, Epworth Sleepiness Scale (ESS), and the Women's Health Initiative Insomnia Rating Scale. Each patient was provided with an actigraph and a sleep diary and instructed to use them for seven days. Actigraphy data was interpreted by blinded investigators using ActiLife actigraphy reading software. Results: 44 of 50 patients returned a completed actigraphy device and diary with at least 3 days of data. 26 patients were recruited in the Caucasian group and 18 patients were recruited in the minority group (16 AA and 2 Hispanic). Baseline characteristics revealed an elevated median CRP (10 vs. 1.8, p=0.006) and Harvey Bradshaw Index (0.5 vs 0, p=0.008) in minority patients. Consistent with previously reported data, there was a trend towards an increased ESS (median 7.0 vs. 4.5) and PROMIS-8a score (median 50.1 vs. 46.7) in minority patients. Upon analysis of actigraphy data, the median sleep efficiency recorded was 81.3 percent for Caucasians and 73.57 percent for minority patients (p=0.05). Wake after sleep onset times showed a trend towards elevation in minority patients (117.01 minutes in minorities vs. 77.3 in Caucasians, p=0.09). Conclusion: This study provides objective evidence for reduced sleep quality in minority patients with IBD using actigraphy. Further studies to confirm these findings and explore the etiology behind this disparity of sleep quality among races is indicated. Support (If Any): None.